2021
DOI: 10.1186/s13006-021-00369-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gestational diabetes mellitus on the duration of breastfeeding in primiparous women: an observational cohort study

Abstract: Background The impact of gestational diabetes mellitus (GDM) on the duration of breastfeeding varies between shortening and no impact. Breastfeeding seems to reduce both maternal and offspring risk for type 2 diabetes and offspring risk for overweight or obesity later in life. The aim of our study was to evaluate in primiparous women whether GDM had an influence on the duration of breastfeeding, and further, to evaluate the factors that influenced on the duration of breastfeeding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Our findings showed that the provision of health education about GDM, especially for young women, even before the planned pregnancy, is extremally important. Our conclusions are in line with an observational study on a Finnish cohort by Laine et al [102], who showed that information about the positive impact of breastfeeding, namely reducing the risk of the development of glucose intolerance and type 2 diabetes mellitus, on the later life of mothers and their children should be provided for young, poorly-educated, overweight women.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings showed that the provision of health education about GDM, especially for young women, even before the planned pregnancy, is extremally important. Our conclusions are in line with an observational study on a Finnish cohort by Laine et al [102], who showed that information about the positive impact of breastfeeding, namely reducing the risk of the development of glucose intolerance and type 2 diabetes mellitus, on the later life of mothers and their children should be provided for young, poorly-educated, overweight women.…”
Section: Discussionsupporting
confidence: 92%
“…Interested participants were put in contact with the research team A purposive sample of 27 women who had been diagnosed with GDM and who initiated breastfeeding between October 2013 and January 2014 Breastfeeding experience data • Focus groups: Audio recorded, transcribed, and noted taken by a member of the research team • Interviews: Audio recorded, transcribed, and noted taken by a member of the research team • Questions used as prompts to initiate conversation and to provide structure • Session’s audio recorded Maternal data • Participant completed surveys • Breastfeeding challenges and breastfeeding support - 44% ( n = 12) of women used formula to manage breastfeeding challenges • Milk supply challenges - Delayed lactogenesis II was reported by 41% ( n = 11) of women - Perceived decreased supply reported by 44% ( n = 12) of women • Concern of infant health - 33% ( n = 9) infants experienced complications including (15% ( n = 4) with hypoglycaemia and 7% (n = 2) with jaundice) • Small study sample size, limiting the transferability of the study findings • No operational definitions for breastfeeding 30.5/40 (76.25%) (Kachoria & Oza-Frank, 2014) [ 51 ] Factors associated with breastfeeding at discharge differ by maternal diabetes type United States To investigate the factors associated with breastfeeding initiation in mothers with gestational and prepregnancy diabetes vs those without diabetes Retrospective cohort study 875,988 births in Ohio between 2006 and 2011. After removal of births not meeting the study inclusion criteria, 792,730 were used in this analysis Maternal, infant, and breastfeeding data Birth certificates The association of maternal and infant characteristics including maternal prepregnancy weight, maternal age, maternal race, prepregnancy care, county type, and infants gestational age on breastfeeding initiation, varied by maternal diabetes status Overweight mothers with a history of GDM were equally likely to breastfeed compared with mothers of normal weight, with a history of GDM • OR 0.95; 95% CI 0.87, 1.03 â likelihood of mothers with a history of GDM, from Appalachian countries, to breastfeed, compared to mothers with a history of GDM from suburban countries • OR 0.7; 95% CI 0.7, 0.8 â likelihood of mothers with a history of GDM who receive inadequate care to breastfeed, compared to mothers without a history of GDM • OR 0.8; 95% CI 0.7, 1.0 • Accuracy of birth certificate data not well researched in Ohio • Method of GDM diagnosis unknown • Limited information available regarding maternal complications of pregnancy and delivery • Lacks specific data about breastfeeding practices • No operational definitions for breastfeeding 34/40 (85%) (Laine et al, 2021) [ 52 ] Impact of gestational diabetes mellitus on the duration of breastf...…”
Section: Resultsmentioning
confidence: 99%
“…Loewenberg Weisband et al found that regardless of GDM, breastfeeding duration was similar when comparing exclusive breastfeeding intentions and by hospital supplementations [ 53 ]. Laine et al also reported no differences in the duration of breastfeeding when comparing women with GDM (7.5 months [SD 3.7]) and those without GDM (7.9 months [SD 3.7]) ( p = 0.17) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking during pregnancy, gaining excessive weight during pregnancy and delivering by caesarean section have all been negatively associated with breastfeeding [ 12 , 13 , 14 ]. Gestational diabetes mellitus, premature birth and high parity may also unfavourably affect breastfeeding success [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%